SERS substrates fabricated with star-like gold nanoparticles for zeptomole detection of analytes1. Issue 22 (14th June 2015) - Pérez-Mayen, Leonardo; Oliva, Jorge; Torres-Castro, Alejandro; De la Rosa, Elder
<x xml:space="preserve">Abstract</x> This work presents the design of substrates for Surface Enhanced Raman Scattering (SERS) using star-like gold nanoparticles which were synthesized using a wet chemical method and functionalized with 1-dodecanethiol.